FAKTOR RISIKO TINGKAT STRES PADA IBU NIFAS DI WILAYAH KERJA UPT PUSKESMAS LEGUNG TIMUR KECAMATAN BATANG–BATANG KABUPATEN SUMENEP TAHUN 2014 - Fitriyah Amin Daman; Sri Yunita Suraida Salat (Fakultas Ilmu Kesehatan, 2015)
Symptoms of postpartum stress include anxiety, lack of confidence,less feel receivingnewborns,fatigue, low self esteem,too sensitive, very irritable, and restless. The incidence ofStress PostPartum quite high at 26.00% - 85.00% (Kasdu, 2003). Many factorsaffect theoccurrence of stress on postpartum mothers. The purpose of this study was toanalyze therisk factors for postpartum maternal stress levels in the working area UPTPHC LegungEastern District of Batang - Trunk SumenepYear 2014.This study is an observational analytic studyDesign using cross sectional method.Population in researchThis is the entire Working Area puerperal women in East Legung UPTPuskesmasSubdistrictSumenep trunks of 20 people. Large sampleis 15 people. Thevariables of this research are: The level of stress,Level of education, age, parity andeconomic level. Data collectionusing a questionnaire DASS 42. The data will be analyzedusing the testSpearman correlation.Based on data analysis known that age has a valuep = 0.001; educational factors with avalue of p = 0.001; parity factor, p = 0.002; factoreconomic level has a value of p = 0.007.This suggests that factorsIt has a significant relationship with the level of stress for women.The role of the family and health workers are needed. Endorsementmorally andfinancially for the family can be given puerperal women and the active rolehealth workersneed to be activated in order to provide guidancereduce the incidence of postpartummaternal stress.Keywords : Stress, postpartum, postpartum mothers